المهارات الحياتية المتضمنة في محتوى منهج العلوم للصف الخامس الأساسي في الجمهورية اليمنية - Al-Hidabi, Dawood Abdulmalek Yahya; Alnaser, Khulood (2018)

(untitled)
The study aims at investigating the extent to which life skills are included in grade five science textbook in Yemen. Based on the literature review a draft list of life skills in similar science textbooks for first grades in primary schools was prepared. A category system was developed for the purpose of content analysis. Validity and reliability were ensured for the content analysis tool. Then 12 units of the Yemeni science textbook were analyzed. The results showed that both hands on and preventive skills were included highly. Environmental skills were of medium inclusion where food and health skills were reported of low inclusion. At the end of the study, it was recommended that life skills have to be included in a balanced way. Food and health life skills have to be enhanced for its low inclusion and their significance in pupils’ lives.